Bonds and mentalization capacity in parental alienation‏ - Faccini, Andréa; Ramires, Vera Ramires Röhnelt (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2013)
This study has focused some of the psychological processes presents in the Parental Alienation, more specifically the characteristics of bonds between fathers, mothers and their children, who are involved in this phenomenon, and their mentalization capacity. An exploratory qualitative study has been conducted, adopting the Multiple Cases Study procedure. Participants were four children and their parents. Participants were sent to psychological evaluation in an university school clinic localized at metropolitan region of Porto Alegre, by the Family Court of the city concerned. The participant’s evaluation process included semi-structured, structured interviews, and psychological tests. The main findings indicated weak and inconsistent affective bonds, permeated by conflicts, and indicators of insecure attachment. Mothers and fathers, as soon as children, showed a restricted mentalization capacity.